PRAGMA-STYLISTICS IN CINDERELLA MOVIE: AN ANALYSIS OF SPEECH ACTS AND FIGURES OF SPEECH AND THEIR IMPLICATIONS FOR ENGLISH LANGUAGE TEACHING - Karunia Eka Nafilatul Janah; Slamet Setiawan (English Education Department at FKIP Nommensen University, 2026)
An utterance having pragma-stylistics elements has to be interpreted well because how the speakers communicate and the hearers interpret cannot simply be defined from the language features or the meaning of the words. This research aims at analyzing pragma-stylistics strategies by main characters in a movie, the elements of the pragma-stylistics strategies in the story plot of the narrative stages in the movie, and the pedagogical implications of the pragma-stylistics strategies toward English Language Teaching (ELT). This descriptive qualitative research obtained the data from Cinderella movie. The pragmatics elements consist of speech acts, while the stylistics elements consist of figures of speech. The results show that there are 43 pragma-stylistics strategies that contain of 32 speech acts and 11 figures of speech in Cinderella movie. The results also show that the pragma-stylistics contribute the story plot of the narrative stages in Cinderella movie that can be seen in all parts of the movie plot; exposition, complication, crisis, climax, and resolution. Last but not least, the pedagogical implication of this study found that the pragma-stylistics strategies are also useful in learning context since it offers some concrete and classroom-ready activities for ELT.